Evolução do Manto de Intemperismo Laterítico Rico em Fosfatos na Ilha de Itacupim (PA) - Mineralogia, Micromorfologia e Geoquímica - DE TOLEDO, MARIA CRISTINA MOTTA; DE OLIVEIRA, SONIA BARROS; DA COSTA, MARCONDES LIMA; PASSOS, CAMILA; DE ALMEIDA, HENRIQUE DINIZ (Pesquisas em Geociências, 2006)
<!– .p text-align: justify; –> The lateritic mantle overlying ultramafic rocks at Itacupim Island (state of Pará, northern Brazil) comprises 5 horizons. From bottom to top they are: (1) altered rock (hornblende, phlogopite, apatite, magnetite, fissural wavellite, and smaller amounts of smectite or kaolinite), (2) a smectitic saprolite (smectite, wavellite, goethite, and traces of hornblende), a kaolinitic saprolite (kaolinite, wavellite, goethite, and traces of phlogopite), a phosphatic duricrust (crandallite, goethite and hematite), and a ferruginous duricrust (hematite, goethite and crandallite). The mineralogical and chemical composition of the saprolitic and duricrust horizons indicate a discontinuity in the weathering evolution: the P-rich crandallitic duricrusts cannot be derived from the P-poor wavellitic saprolites. Most probably, the duricrusts developed during an earlier stage of the weathering evolution, under a drier climate, when the hypogene phosphates (wavellite and apatite) transformed into crandallite. Under subsequent more humid conditions, the weathering alteration of the parent rock led to the dissolution of the hypogene phosphates, resulting in the P-depleted saprolites.